„A jog őrzőinek államok közötti együttműködése”: Transzferfolyamatok és kölcsönhatások a náci rendszer és Magyarország jogászai között - Schumann, Eva (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2025)
The article deals with the transnational interactions, co-operations and discourses between German and Hungarian jurists during the ‘Third Reich’, especially from a German perspective. It ranges from visiting professorships on the basis of the German-Hungarian Cultural Agreement (1936) to publications by Hungarian jurists in German journals to the foreign relations of the Akademie für Deutsches Recht (Academy for German Law) as well as to the work of two internationally oriented German institutions at the beginning of the 1940s, namely the Internationale Rechtskammer (International Chamber of Law) and the Internationale Akademie für Staats- und Verwaltungswissenschaften (International Academy of Political and Administrative Sciences), which both focused primarily on the European ‘Großraum’. The article traces the German efforts to promote Nazi law abroad and discusses the legal harmonisation (especially in the areas of commercial and administrative law) within the ‘Großraum’, which was pursued under German leadership after the beginning of the Second World War. Overall, it is shown that all activities on the German side did not focus on academic exchange, but primarily on implementing the political interests of the Nazi regime.